2012
DOI: 10.1097/ta.0b013e318270dcf5
|View full text |Cite
|
Sign up to set email alerts
|

A standardized rapid sequence intubation protocol facilitates airway management in critically injured patients

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…In fact, the available adult sedation data regarding ketamineincluding cases in which the drug is administered in environments even more austere than the prehospital/HEMS setting-suggest both safety and efficacy of dissociative anesthesia in nonpediatric patients [26,27]. Emerging literature describing ketamine's use for trauma ETI in the ED is also suggesting the safety and even preferability of the agent, based on both physiology and simplicity (ie, single anesthetic plus NMB) [17].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In fact, the available adult sedation data regarding ketamineincluding cases in which the drug is administered in environments even more austere than the prehospital/HEMS setting-suggest both safety and efficacy of dissociative anesthesia in nonpediatric patients [26,27]. Emerging literature describing ketamine's use for trauma ETI in the ED is also suggesting the safety and even preferability of the agent, based on both physiology and simplicity (ie, single anesthetic plus NMB) [17].…”
Section: Discussionmentioning
confidence: 97%
“…In fact, German experts have called for preferential use of ketamine over etomidate for trauma airway management, owing to etomidate's potential effects on the adrenal axis [23]. Although recent data [17] suggest that there may be a change toward more frequent use of ketamine for trauma ETI in the ED setting in the United States, multicenter airway management studies have suggested that ketamine is not commonly used for airway management [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study detected significant differences between pre-and post-ketamine MAP (Table 3) but not HR. Ballow et al [28] compared the outcomes in 177 patients who received a ketamine protocol for RSI to 266 patients who received pre-protocol regimens that included midazolam, fentanyl, and etomidate with a muscle relaxant and reported hypotension in only 3.6% of patients in the ketamine group compared to 6 % in the nonketamine group. Their study, despite the reasonable sample size, reported significantly lower hypotensive events than our study.…”
Section: Ketamine-induced Changes In Blood Pressure and Heart Rate Inmentioning
confidence: 99%
“…Ketamine is useful in asthma and reactive airways disease for reducing bronchospasm associated with intubation [4,13]. Use in TBI has been limited previously because of concerns for the increased ICP; yet, recent reviews on the topic have called into question that the evidence behind the proscription against use of ketamine in the head-injured patient [17][18][19][20]. In neurotrauma, ketamine may have neuroprotective properties [19 • ].…”
Section: Ketaminementioning
confidence: 99%